2014
DOI: 10.1097/scs.0000000000000603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perioperative Remifentanil With Controlled Hypotension on Intraoperative Bleeding and Postoperative Edema and Ecchymosis in Open Rhinoplasty

Abstract: Remifentanil with controlled hypotension may reduce edema and ecchymosis of the upper and lower eyelids, by reducing mean arterial pressure and amount of bleeding in rhinoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Different surgical approaches have been reported in the literature to decrease these complaints to a minimal level. 10 A variety of medical analyses 11 and different anesthetic agents have been used for this purpose. 12 Nevertheless, there is no consensus on the mechanism of production of these complaints because it is believed to be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Different surgical approaches have been reported in the literature to decrease these complaints to a minimal level. 10 A variety of medical analyses 11 and different anesthetic agents have been used for this purpose. 12 Nevertheless, there is no consensus on the mechanism of production of these complaints because it is believed to be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different pharmacological agents were tested to reduce postoperative edema. 5,8 Platelet concentrates have been widely used in the last two decades, especially in dental and orthopaedic procedures. Since many growth factors and cytokines are available in PRF, its clinic effects on tissue healing have been defined for many clinic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that preoperative administration of steroids reduced edema and ecchymosis, and repeated administration of steroids was more effective than administration of a single dose (5,14). A study performed by Koşucu et al reported that keeping intraoperative mean arterial blood pressure at 50-60 mmHg reduced edema and ecchymosis (15). There are some studies about topical administration of arnica and mucopolysaccharide polysulfide cream, which reduces edema and ecchymosis (16).…”
Section: Discussionmentioning
confidence: 99%
“…The grade of edema and ecchymosis is affected by many traits of the patient as well as by surgical interventions and techniques. Edema and ecchymosis are more common in patients with hypertension, bleeding diathesis, and less subcutaneous fatty tissue, as well as in light-skinned patients (15).…”
Section: Discussionmentioning
confidence: 99%